Direct loss and expense relating to remoteness of damages - Lee, Xia Sheng (2006)
Direct loss and expense is a very important element in construction contracts. However, due to the imbalance relationship between employer and contractor, direct loss and expense is taken lightly and often treated as a mere â€œbusiness decisionâ€. Direct loss and expense is closely related to Section 74(1) and (2), Contract Act 1950, which similar to the rule in Hadley v Baxendale. This study is aimed at reducing the uncertainty and difficulties in the event of claiming direct loss and expense that is deny under the reason of â€œremote and indirect loss or damageâ€. This study is carried out to determine whether direct loss and expense is related to remoteness of damages and which limb of rule of Hadley v Baxendale, each head of claims lies under. The head of claims include loss of profit, finance charges, overheads and loss of productivity. This study was carried out mainly through documentary analysis of law journals. It was found that loss of profit falls under both limbs of Hadley v Baxendale. loss of profit under special circumstance is claimable, provided there is contemplation at the beginning about such arrangement. The other three head of claims fall under the first limb of Hadley v Baxendale, claimable if they are cause by employerâ€™s interruption arising naturally in the course of running a operation. It is hoped that it may provides some rough ideas or guidelines for the parties in the construction industry on direct loss and expense